Penulis Novel Online dalam Kajian Dramaturgi - Yeni Fitri; T. Romi Marnelly (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The development of technology is developing very rapidly, the ease of this technology has created a new era in the literary world that makes it easier for everyone to hone and become a writer. This research aims to find out the life of online novelists in building a front stage on social media, backstage life in their daily lives and social and economic impacts. Through a descriptive qualitative approach using the snowball sampling technique. Data collection was carried out by observation, interviews and documentation. The results of this study show that online novel writers consciously form and manage their identities consciously in the digital space. In the front page, it can be seen how an online novel writer manages his identity through the use of pen names and also how to interact with readers without the need to see his life behind the scenes. While the back stage includes creative activities carried out by the writer, personal routines that are not in finding ideas and also the original personality. The dramaturgy carried out by online novel writers shows that the social role as a writer is still more dominant in the digital space than in their real lives. A self-image that is built consistently and sustainably allows access to economic opportunities that can help and improve the author's economic status.